(untitled) (Journal of Parents and Teachers, 2024)
The article highlights the importance of education in the socialization and development of the individual, emphasizing the role of the family and the collaboration between parents and educators. Insufficient socialization is mentioned as a problem and the use of multiple texts to enrich teaching and foster values is emphasized. Communication and joint efforts are essential to improve education.